2017
DOI: 10.1016/j.cyto.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/Enhancer-binding protein β promotes pathogenesis of EAE

Abstract: The CCAAT/Enhancer Binding Protein β (C/EBPβ) transcription factor is activated by multiple inflammatory stimuli, including IL-17 and LPS, and C/EBPβ itself regulates numerous genes involved in inflammation. However, the role of C/EBPβ in driving autoimmunity is not well understood. Here, we demonstrate that Cebpb−/− mice are resistant to EAE. Cebpb−/− mice exhibited reduced lymphocyte and APC infiltration into CNS following EAE induction. Furthermore, MOG-induced Th17 cytokine production was impaired in drain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…For M1 polarization, it was demonstrated that CEBPβ is upregulated in macrophages in response to IFNγ, IL-1, IL-6, TNF, and LPS and induce expression of M1 markers ( 40 ). CEBPβ is also required for induction of Th1/Th17-mediated autoimmune neuroinflammation associated with M1/M2 mixed macrophages activation ( 9 , 41 ). Our study suggests that Egr2 upregulate expression of M1 and M2 markers through activation of CEBPβ and its downstream targets.…”
Section: Discussionmentioning
confidence: 99%
“…For M1 polarization, it was demonstrated that CEBPβ is upregulated in macrophages in response to IFNγ, IL-1, IL-6, TNF, and LPS and induce expression of M1 markers ( 40 ). CEBPβ is also required for induction of Th1/Th17-mediated autoimmune neuroinflammation associated with M1/M2 mixed macrophages activation ( 9 , 41 ). Our study suggests that Egr2 upregulate expression of M1 and M2 markers through activation of CEBPβ and its downstream targets.…”
Section: Discussionmentioning
confidence: 99%
“…NINJ1 functions in cell adhesion and inflammation, such as leukocyte migration to sites of inflammation in the endothelium. CEBPB is a transcription factor that plays diverse roles in inflammation, e.g., through T helper cell 17 (T H 17)-dependent regulation of inflammation in models of multiple sclerosis [71]. The CEBPB gene has already been described as a vitamin D target in myeloid leukemia cells [72].…”
Section: Discussionmentioning
confidence: 99%
“…The Tax protein of human T-cell leukemia virus type 1 (HTLV-1) activates the human IL-17 promoter via CREB pathway (39). In addition, IL-17 production is remarkably reduced in C/EBP␤ Ϫ/Ϫ mice (40). In our study, we found that C/EBP␤ and CREB are required for PRRSV-induced IL-17 production.…”
Section: Discussionmentioning
confidence: 56%